The Oghams on the Brodie and Aquhollie Stones, with Notes on the Inscriptions of the Golspie and Newton Stones, and a List of the Oghams in Scotland - Southesk, Earl of (Proceedings of the Society of Antiquaries of Scotland, 1886)